Senior management characteristics and firm performance: An application of upper echelons theory to firms listed on the JSE - Winslow, Tyron (University of the Witwatersrand, Johannesburg, 2021)
Upper echelons theory states that the background and characteristics of an firm’s senior management has an impact on its operations and performance. This study applies the upper echelons theory to the largest 100 JSE listed firms by market capitalisation. For these firms, the study explored the relationships between performance and senior management characteristics using panel data from 2015 to 2019 in a regression. The performance of the firms as indicated by share price, return on assets and Tobin’s Q were regressed on characteristics of qualifications, age, tenure and professional accreditation. The findings indicate that the performance of firms has no significant relationship with the above senior management characteristics. There was a negative relationship identified between the qualifications of the senior management and the financial performance of the firm suggesting a slight better performance by those less qualified. Further there appears to be a negative relationship between the financial performance of the firm and whether the senior management are accredited to a professional body. This suggests that firms whose senior management are found not to be affiliated to a professional body are outperforming those that are affiliated with a professional body. These findings have potential implications for the investment community whose investment criteria may include management characteristics.
A research report submitted in fulfillment of the requirements for the Master of Commerce, in the Faculty of Commerce Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; accreditations; qualifications; age; tenure; share price; Tobin’s Q; return on assets; upper echelons theory; SDG-8: Decent work and economic growth